Cognitive Behavioral Counseling Vs Family Counseling: Which Motivational Interviewing Is More Effective to Reduce Game Addiction in Adolescents? - Wiryo Nuryono (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
Game addiction is a phenomenon that can interfere with adolescents’ social relationships, leading to emotional, behavioral or mental disorders. The COVID-19 pandemic has contributed to an increase in game addiction behavior, largely due to feelings of loneliness. The consequences faced by adolescents as a result of game addiction can significantly impact their personal, social, learning, and career aspects. Therefore, it is crucial to employ appropriate counseling techniques to effectively reduce this addiction. Empirical and practical evidence showed that Family Counseling and Motivational Interviewing Techniques were effective in addressing game addiction. This study aimed to show the effectiveness of the Family Counseling Motivational Interviewing (FCMI) technique in reducing game addiction, as compared to Cognitive Behavioral Counseling (CBC). A quantitative approach was utilized, with a randomized controlled trial as the study design. The hypothesis was analyzed using the Wilcoxon and Mann-Whitney Tests. A total of 90 adult students participated in this study and were classified into FCMI as the experimental group and the CBC as the control. The results showed that the FCMI technique was more effective in reducing game addiction than CBC. Significant improvements were also observed in the aspects of tolerance and mood modification, which experienced a notable decrease.